Cognitive Training for Agility: The Integration Between Perception and Action. Issue 1 (February 2018) - Spiteri, Tania; McIntyre, Fleur; Specos, Christina; Myszka, Shawn
Abstract : ABSTRACT: AGILITY IS A KEY FEATURE WITHIN MANY STRENGTH AND CONDITIONING PROGRAMS, WITH THE DEVELOPMENT OF ATHLETE'S PHYSICAL AND TECHNICAL QUALITIES BEING THE PRIMARY FOCUS TO INCREASE PERFORMANCE. HOWEVER, THIS APPROACH IS SOMEWHAT LIMITED AS TRUE RETENTION AND TRANSFER OF PERFORMANCE FROM TRAINING TO SPORT CANNOT BE ACHIEVED UNLESS COACHES DEVELOP AN ATHLETE'S ABILITY TO IDENTIFY RELEVANT STIMULI AND LEARN TO ADAPT MOVEMENT IN RESPONSE TO VARYING CONSTRAINTS. THE PURPOSES OF THIS ARTICLE ARE TO DISCUSS THE CONSTRAINTS ACTING ON THE ATHLETE AND PROVIDE EXAMPLES OF HOW THESE CAN BE MANIPULATED TO ENHANCE INFORMATION-MOVEMENT COUPLING DURING TRAINING TO IMPROVE THE OVERALL AGILITY PERFORMANCE.